Mycoplasma Pneumoniae Infection and Persistent Wheezing in Young Children: A Retrospective Case-Control Study - Sun, Huiming; Li, Shuxiang; Wang, Ting; Chen, Zhengrong (Frontiers in Pediatrics, 2022)
Background: To investigate the clinical characteristics of children with persistent wheezing (PW) with Mycoplasma pneumoniae (MP) DNA in bronchoalveolar lavage fluid (BALF). Methods: This retrospective case-control study included consecutive admitted children under 3 years of age who were diagnosed with PW and had MP DNA detected in BALF. Patients with mycoplasma pneumoniae pneumonia (MPP) and foreign-body aspiration (FBA) were enrolled as controls. The clinical characteristics of the groups were compared. Results: During the study period, there were 89 patients diagnosed with PW without structural anomalies of the conductive airways, and 30 of these patients (33.7%, 30/89) with MP DNA detected in the BALF were selected as the study group. We included 44 patients with MPP and 44 patients with FBA as controls. Patients with MPP were older and had a higher occurrence of fever and C-reactive protein (CRP) than patients with PW (all P<0.001). The median MP DNA copy number in patients with MPP was higher than that of patients with PW (P=0.004). The median level of MP IgG in patients with PW was lower than that of patients with MPP and higher than that of patients with FBA (all P<0.001). MP DNA copy number positively correlated with age (r=0.392, P=0.001) and CRP (r=0.235, P=0.048). Conclusions: Our study reveals that MP was highly detected in the BALF of PW patients. In addition, young patients with a low load of MP infection showed lower amounts of antibody, and a weak inflammatory response might be associated with PW.